Improvement of Endoglucanase Activity in Penicillium oxalicum ID10-T065 Mutated by Ultra Violet Irradiation and Ethidium Bromide - Caniago, Asnany; Mangunwardoyo, Wibowo; Nuswantara, Sukma; Lisdiyanti, Puspita (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2015)
Penicillium sp. is known as filamentous fungi that produce complete cellulase. Cellulase. This study aims to improve endoglucanase activity of Penicillium oxalicum ID010-T065 by mutated with ultra violet irradiation (with dose of 0.1 J/cm2, 15 cm), ethidium bromide (10 µg/mL, 1 hour) and combination of both mutagens. The endoglucanase activity of all mutants was higher than that of the wild type (1.03 U/mL). Mutant UVEB-42 exposed to combine mutation showed the highest endoglucanase activity (2.76 U/mL) with a 2.70 fold increase. Mutant EB-45 (1.83 U/mL) exposed to ethidium bromide solution showed a 1.8 fold increase. Mutant UV-13 (1.72 U/mL) exposed to UV irradiation for 3 minutes showed a 1.7 fold increase. All mutants have optimum endoglucanase activity at 50 °C. Mutant UVEB-53 showed the highest thermostability by retaining 86 % of endoglucanase activity at 90 °C. The gene analysis of the endoglucanase I gene showed 3 bases mutated at mutant UV-13 and UVEB-53 that changed proline to serine. Mutant EB-45 showed 4 bases mutated that changed valine to glysine and proline to serine. Two bases mutated at Mutant UVEB-53 changed proline to serine. Bases mutated in eg1 gene could influenced the enhance of enzym activity in mutant.